2021
DOI: 10.1080/21655979.2021.1995103
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine suppresses tumor biological characteristics of human hepatocellular carcinoma via inhibiting IGF-1R/PI3K/AKT/mTOR signaling axis

Abstract: Ropivacaine, a common local anesthetic in the clinic, has anti-proliferative and pro-apoptotic effects in numerous cancers, however, the underlying regulatory mechanism of ropivacaine in hepatocellular carcinoma remains unclear. In the current study, human HepG2 cells were stimulated with different ropivacaine concentrations. Cell Counting Kit-8 assay, cell colony formation, and cell cycle were used to monitor cell viability. Cell apoptosis, migration, and invasion were determined by flow cytometry and transwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Ropivacaine has been showed to promote the apoptosis of numerous cancer cells including breast cancer, hepatocellular carcinoma cancer, and colon cancer [12][13][14][15]. Our ndings are consistent with above, ropivacaine combined with cisplatin signi cantly increase apoptosis in cisplatin-sensitive and cisplatin-resistant colon cancer cells when compared to cisplatin alone treatment.…”
Section: Introductionsupporting
confidence: 91%
“…Ropivacaine has been showed to promote the apoptosis of numerous cancer cells including breast cancer, hepatocellular carcinoma cancer, and colon cancer [12][13][14][15]. Our ndings are consistent with above, ropivacaine combined with cisplatin signi cantly increase apoptosis in cisplatin-sensitive and cisplatin-resistant colon cancer cells when compared to cisplatin alone treatment.…”
Section: Introductionsupporting
confidence: 91%
“…Wang et al [26] found that ropivacaine could interact with ITGB1 protein and inhibit the expression of ITGB1 protein in colon cancer cells, thereby affecting its downstream Akt and ERK signaling pathways. Also, at the molecular level, Zhang et al [42] have demonstrated that in the tumor xenograft experiment, ropivacaine was confirmed to inhibit tumor growth, accompanied by inhibition of the IGF-1 R/PI3K/AKT/mTOR signaling axis. Even at the transcriptional level, Zhang et al [15] confirmed that ropivacaine inhibited the proliferation, migration, invasion and increased apoptosis of GC cells by upregulating the expression of miR-520a-3p and further regulating the WEE1 and PI3K/AKT signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine down-regulated PI3K/Akt pathway via the reduction of ubiquitin specific peptidase 14 (USP14) level, leading to lower-level proliferation and invasion capacity (54). Similarly, ropivacaine and bupivacaine both could suppress PI3K/Akt pathway and reduce tumor cell proliferation and metastasis (55,57). Other pathways like MAPK can also be downregulated with LA treatment and involved in HCC progression (55).…”
Section: Local Anestheticsmentioning
confidence: 99%